1997
DOI: 10.1128/iai.65.8.3080-3085.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among clinical and environmental isolates of Aspergillus fumigatus

Abstract: To determine if cases of invasive aspergillosis (IA) were caused by strains of Aspergillus fumigatus with unique characteristics, strains from immunosuppressed patients with IA were compared to strains obtained from sputa of patients with cystic fibrosis and to strains from the environment. An extremely high genomic diversity was observed among the 879 strains typed by Southern blotting with a retrotransposon-like element from A. fumigatus (C. Neuvéglise, J. Sarfati, J. P. Latgé, and S. Paris, Nucleic Acids Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
3
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 27 publications
7
79
3
2
Order By: Relevance
“…Our inability to discover any correlation between genotype and geography in a global collection of A. fumigatus individuals makes this fungus the first to be shown by population genetic evidence to have a global population structure with no endemism. Our result is consistent with earlier studies of more limited scope, for example, no correlation was found between genotype and geography for European and North American individuals (Debeaupuis et al 1997), nor for isolates from French and Italian patients (Bertout et al 2001), nor for environmental and clinical isolates from Canada (Rosehart et al 2002). Neither has any correlation between genotype and geography been found in another, study using a different collection of A. fumigatus individuals and different genetic markers (Rydholm et al 2003).…”
Section: Biogeographysupporting
confidence: 92%
See 3 more Smart Citations
“…Our inability to discover any correlation between genotype and geography in a global collection of A. fumigatus individuals makes this fungus the first to be shown by population genetic evidence to have a global population structure with no endemism. Our result is consistent with earlier studies of more limited scope, for example, no correlation was found between genotype and geography for European and North American individuals (Debeaupuis et al 1997), nor for isolates from French and Italian patients (Bertout et al 2001), nor for environmental and clinical isolates from Canada (Rosehart et al 2002). Neither has any correlation between genotype and geography been found in another, study using a different collection of A. fumigatus individuals and different genetic markers (Rydholm et al 2003).…”
Section: Biogeographysupporting
confidence: 92%
“…Our data support the hypothesis that any isolate of either the ''fumigatus'' or the ''occultum'' clade is a potential pathogen, an idea originally formulated from European and North American collections of A. fumigatus (Debeaupuis et al 1997, Bart-Delabesse et al 1998, see also Rosehart et al 2002). These taxa are accidental human pathogens and are not transmitted from host to host; infection provides no apparent benefit to the fungi.…”
Section: Cryptic Speciessupporting
confidence: 79%
See 2 more Smart Citations
“…It is important to remember that genetic analysis cannot discriminate between clinical and environmental isolates of A. fumigatur, indicating that every strain present in the environment is a potential pathogen if it encounters the appropriate host [32]. Thus, the degree of exposure assessed by CFUs per unit of ambient air is not predictive of disease; the actual risk appears to vary with the underlying condition.…”
Section: Air Quality Maintenancementioning
confidence: 99%